Resistance gene profiling of beta-lactamase and carbapenemase in gram-negative blood isolates: A tertiary care hospital - Daniel Beshah; Tesfaye Sisay Tessema; Gurja Belay Woldemichael; Esmael Besufikad Belachew; Dawit Hailu Alemayehu; Abebech Tesfaye; Dessalegn Abeje Tefera; Solomon Gizaw Derese; Tizazu Zenebe Zelelie; Abera Admasie; Tamrat Abebe; Adey Feleke Desta (PLoS ONE, 2026)
The global rise in antimicrobial resistance is largely driven by DNA-encoded, antibiotic-hydrolyzing enzymes. This study aimed to determine the prevalence of ESBL, AmpC-BL, MBL, and carbapenemase genes. A cross-sectional study was conducted from September 2018 to March 2019 using standard microbiological and molecular methods. Among 231 Gram-negative bacterial isolates, 176 (76.2%) carried beta-lactamase genes confirmed by PCR. ESBLs were detected in 117 (50.6%), MBLs in 50 (21.6%), carbapenemases in 46 (19.9%), and AmpC-BLs in 22 (9.5%). The most frequent carriers were Klebsiella pneumoniae , Escherichia coli , and Acinetobacter species . The dominant ESBL genes were blaCTX-M (85.2%) and blaTEM (79.5%), with blaBEL (17.2%) surpassing blaSHV (9.8%), indicating a shift in resistance patterns, while among AmpC genes, blaFOX (39.4%) and blaCITM (36.4%) were the most prevalent. The blaOXA-23 (40.6%) and blaKPC (14.5%) were the most common carbapenemase genes, while blaNDM (39.1%) and blaVIM (34.8%) dominated among MBLs. The high prevalence of blaOXA-23 in Ethiopia is a significant finding, which I have not found evidence of in similar African or Asian settings. A comparable trend in Taiwan suggests medical tourism may contribute to the spread of resistant bacteria. These findings highlight the critical importance of continuous molecular surveillance and indicate that factors like medical tourism may contribute to the international dissemination of resistant strains.